2023
DOI: 10.1021/acsnano.2c07607
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Engineered Immune Cells and Bacteria as Drug Carriers for Cancer Immunotherapy

Abstract: Immunotherapy continues to be in the spotlight of oncology therapy research in the past few years and has been proven to be a promising option to modulate one's innate and adaptive immune systems for cancer treatment. However, the poor delivery efficiency of immune agents, potential off-target toxicity, and nonimmunogenic tumors significantly limit its effectiveness and extensive application. Recently, emerging biomaterial-based drug carriers, including but not limited to immune cells and bacteria, are expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 331 publications
(644 reference statements)
0
11
0
Order By: Relevance
“…The rise of biomimetic nanotechnology offers more design options for cancer nanovaccine systems. , Various biomimetic nanovaccines including DC-derived and bacterial-derived nanovaccines have demonstrated desirable therapeutic effects. However, these nanovaccines may face obstacles during the detoxification or antigen pulsing processes . In contrast to other biomimetic cancer nanovaccines, tumor cell-derived nanovaccines exhibit a large spectrum of antigens, allowing the development of diverse cytotoxic lymphocyte repertoires that make it more difficult for tumor cells to evade immune surveillance .…”
Section: Discussionmentioning
confidence: 99%
“…The rise of biomimetic nanotechnology offers more design options for cancer nanovaccine systems. , Various biomimetic nanovaccines including DC-derived and bacterial-derived nanovaccines have demonstrated desirable therapeutic effects. However, these nanovaccines may face obstacles during the detoxification or antigen pulsing processes . In contrast to other biomimetic cancer nanovaccines, tumor cell-derived nanovaccines exhibit a large spectrum of antigens, allowing the development of diverse cytotoxic lymphocyte repertoires that make it more difficult for tumor cells to evade immune surveillance .…”
Section: Discussionmentioning
confidence: 99%
“…BNPs have been explored for their potential use in the treatment of antitumor immunity. [135] To capitalize on the advantages of BNPs, several studies have developed bifunctional BNPs to combine antitumor immunity and PTT. Chen et al successfully synthesized mesoporous polydopamine NPs that demonstrated efficient photothermal performance, high biocompatibility, and rapid biodegradability, making them highly suitable for PTT applications.…”
Section: Cancermentioning
confidence: 99%
“…BNPs have been explored for their potential use in the treatment of antitumor immunity. [ 135 ] To capitalize on the advantages of BNPs, several studies have developed bifunctional BNPs to combine antitumor immunity and PTT. Chen et al.…”
Section: Bacterial Membrane‐coated Nanoparticlesmentioning
confidence: 99%
“…Although the structures and phase behaviors of confined monolayer water within DWCNTs have been systematically investigated by Liu et al,11 to the best of our knowledge the dynamics of this peculiar system are still not explored. The major goal of this work is to reveal the dynamics of monolayer water in DWCNTs by using molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%